COMPETITOR FINANCIAL STATEMENT PERFORMANCE APPRAISAL ANDFINANCIAL PERFORMANCE OF QUOTED MANUFACTURING FIRM IN NIGERIA - Erorogha Akpos Yikarebogha (PhD) (Gusau Journal of Accounting and Finance)
focus of the study is on competitor financial statement performance appraisal and its relationship with financial performance of manufacturing companies in Nigeria. The population of the study is the sixty-nine quoted manufacturing companies in the Nigerian Exchange Group, while sixty (60) of them were used as sample using the purposive sampling technique. The scope of the study covers the period 2014 -2023. Ex-post facto research design was adopted, with data obtained from the financial statements of the different companies involved in the study. Four (4) dimensions of financial performance were used for this study, which are net profit before tax, earnings per share, return on equity and return on assets against competitor financial statement performance appraisal. This led to the formulation of four (4) hypotheses that were tested using spearman rank correlation for the analyses. The results indicated that, while net profit before tax, return on equity and return on assets have significant relationship with competitor financial statement performance appraisal, earnings per share on the other hand, showed an insignificant relationship with competitor financial statement performance appraisal. The study therefore recommended that for companies intending to improve their net profit before tax, return on equity and return on assets, managers of manufacturing firms should engage more on competitor financial statement performance appraisal, while for companies intending to shore up the value of their earnings per share, competitor financial statement performance appraisal is not an option to engage in.